Pembagian Kewenangan dalam Pelayanan Publik antara Pemerintah Pusat dan Pemerintah Daerah - Purwanto, Erwan Agus (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2006)
The implementation of new laws on local autonomy in Indonesia has arisen hopes democracy an better services at the local level. However, these no hopes have not materialized as yer due to various barriers. The local stakeholders are not well prepared with the increasing discretionary powers. They tended to abuse their powers and neglected public interests, which resulted in loss qualified public services. Thing are more complicated as central government officials have not ready to share authorities with their local counterparts. Local government budgets are still depended on subsidies from the central government. It is difficult for the local government to carry out autonomous and efficient public services long as the financial issues are not resolved.